The Temptations of the Dinosaur Theory - Larsmo, Ola (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Does the book have a future? Ola Larsmo firmly discards the common theory that a new medium makes its predecessor obsolete, terming it ‘the temptations of the dinosaur theory’. This has never happened, he argues. The radio did not replace the newspaper, the television did not replace the radio and the cinema, and so on. There always remains a form of coexistence when the new medium can do something in addition to the previous medium; he terms this ‘x plus 1’. Ola Larsmo concludes that the book in its present form will be with us for many years to come, despite of, and as well as, the tremendous growth of digital information.